Structural properties of cationic surfactant-fatty alcohol bilayers: insights from dissipative particle dynamics. Issue 43 (27th October 2021) - Svoboda, Martin; Jiménez S., M. Guadalupe; Kowalski, Adam; Cooke, Michael; Mendoza, César; Lísal, Martin
Abstract : Bilayers, self-assembled by cationic surfactants and fatty alcohols in water, are the basic units of lamellar gel networks – creamy formulations extensively used in cosmetics and pharmaceutics. Abstract : Bilayers, self-assembled by cationic surfactants and fatty alcohols in water, are the basic units of lamellar gel networks – creamy formulations extensively used in cosmetics and pharmaceutics. Mesoscopic modelling and study of the bilayers formed by single- or double-tail cationic surfactants (CTAC or DHDAC), and fatty alcohols (FAs) in the lamellar fluid and gel phases were employed. Fatty alcohols with alkyl tail equal to or greater than the surfactant alkyl tail, i.e., C16 FA or C18 FA and C22 FA, were considered. A model formulation was explored with the FA concentration greater than that of the surfactant and the structure of the fluid and gel bilayers in tensionless state characterised via the density profiles across the bilayers, orientational order parameters of the surfactant and FA chains, intrinsic analysis of the bilayer interfaces, and bending rigidity. The intrinsic analysis allows identification and quantification of the coexistence of the interdigitated and non-interdigitated phases present within the gel bilayers. The FA chains were found to conform the primary scaffolding of the bilayers while the surfactant chains tessellate bilayer monolayers from their water-hydrophobic interface. Further, the overlap of the FA chains from the apposed monolayers of the fluid bilayers rises with increasing FA length. Finally, the prevalence of the non-interdigitated phase over the interdigitated phase within the gel bilayers becomes enhanced upon the FA length increase with a preference of the surfactant chains to reside in the non-interdigitated phase rather than the interdigitated phase.